Bag design : a handbook for accessories designers - Mini Miss Mia; Mini Miss Mia; Chow, Sarah; Yip, Penter (Fashionary, 2016)
"The Fashionary Bag Design is a complete handbook focusing on the practical needs of bag and accessories designers. It provides an insightful and inspirational foundation about bags and their key fundamentals to those in the fashion industry"--amazon.com.